Block and sub-block boundary strengthening in lath martensite. (15th April 2016) - Du, C.; Hoefnagels, J.P.M.; Vaes, R.; Geers, M.G.D.
Abstract: Well-defined uniaxial micro-tensile tests were performed on lath martensite single block specimens and multi-block specimens with different numbers of block boundaries parallel to the loading direction. Detailed slip trace analyses consistently revealed that the {110}<111 > slip system with the highest Schmid factor is activated. Both block and sub-block boundaries act as barriers to dislocation motion, whereby a Hall–Petch like behavior is observed. Sub-block boundary strengthening appears to be only slightly less effective than block boundary strengthening, even though fracture analyses indicate that dislocation motion can cross sub-block boundaries, but not block boundaries. Graphical abstract: